A qualitative exploration of parental perspectives and behaviors on self-medication for children under five in Abbottabad, Pakistan - Haq, Ijaz ul; Hanzila Azhar, Syed; Zakki, Shahbaz Ahmad; Hu, Xiaojing (Frontiers in Pediatrics, 2025)
BackgroundChildren are more susceptible to irrational medication and its short- and long-term health consequences. This study investigated parents' perceptions and behavior regarding self-medication of their children under five years of age in city Abbottabad, Pakistan.MethodsNon-probability convenient random selection was used to select participants for this qualitative study. In-depth interviews were conducted with 40 parents who self-medicate their children, utilizing audio recordings and note-taking as the methods for data collection. N-Vivo 11.0 was used for thematic analysis and data has presented according to COREQ checklist.ResultThe majority (45%) of parents were aged 25–35 years, while 35% had primary education. Of the 40 parents (18 females, 22 males) interviewed, 38 reported frequently self-medicating their children. The data highlighted three major themes: reasons for self-medication, factors influencing self-medication, and most commonly used medication. Parents reported that they self-medicate their children frequently. Most parents kept antipyretics, antibiotics, and cough syrups at home. The majority of the participating parents preferred self-medication due to their lack of trust on healthcare professionals. Factors for self-medication practices included a preference of home-based care, cultural influence, financial and time constraints, the parents' own understanding of the disease and its symptoms, and a lack of basic education.ConclusionPakistani parents in the Abbottabad region frequently resort to self-medication for their children, due to range of factors. The study emphasizes the need of building trust in healthcare experts, raising knowledge and educating people about the dangers of self-medication, and addressing cultural and socioeconomic variables that influence parental decision-making.